Cultural adaptation of a patient decision-aid for insulin therapy - Tan, Ngiap Chuan; Koong, Agnes Ying Leng; Phoon, Ian Kwong Yun; Wang Zhen, Sinead; Paulpandi, Muthulakshmi; Lee, Yew Kong; Furler, John; Car, Josip; Ng, Chirk Jenn (BMJ Publishing Group, 2020)
Introduction Patient decision-aids (PDAs) support patients in selecting evidence-based treatment options. PDA is useful only if the user understands the content to make personalised decisions. Cultural adaptation is a process of adjusting health messages so that the information is accurate, relevant and understandable to users from a different population. A PDA has been developed to assist Malaysian patients with secondary drug failure to initiate insulin therapy to control their type 2 diabetes mellitus (T2DM). Likewise, patients with T2DM in neighbouring Singapore face similar barriers in commencing insulin treatment, which a PDA may facilitate decision-making in selecting personalised therapy. Objective The study aimed to explore the views and perceptions of Singaporean primary care providers on the Malaysia PDA to initiate insulin therapy and described the cultural adaptation process used in the design and development of a new PDA, which would be trialled in a Singapore primary healthcare institution. Method Qualitative research method was deployed to conduct one-to-one in-depth interviews of the healthcare providers at the trial site (SingHealth Polyclinics-SHP), including six primary care physicians and four nurses to gather their views and feedbacks on the Malaysian PDA. The interviews were transcribed, audited and analysed (standard content analysis) to identify themes relating to the content, layout, concerns of the original PDA and suggestions to the design of the new SHP PDA. Results Cultural adaptation of the new PDA includes change to the overall design, graphics (including pictograms), presentation styles, additional contextualised content (personalisation, subheadings, cost and treatment option), modified phrasing of the subtitles and concerns (choice of words) relevant to the new users. Conclusion A PDA on insulin therapy underwent cultural adaptation before its implementation in another population in a neighbouring country. Its relevance and effectiveness will be evaluated in future research. © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.